THE EFFECT OF INCOME, DISTRIBUTION OF FUNDS, AND FEE-BASED INCOME ON THE PROFITABILITY OF BSI INDONESIA - Nurianti Rahmadani; Annio Indah lestari Nasution; Nurwani Nurwani (JURNAL ILMIAH EDUNOMIKA, 2024)
The purpose of this study was to determine the effect of income, distribution of funds, and fee-based income on return on assets at PT BSI Tbk in 2018-2022. In this study aims to determine the effect of Income, Distribution of Funds, and Fee Based Income on ROA (Return On Assets) (Y). The research data was obtained from the results of the publication of the financial statements of PT. BSI Indonesiafrom 2018-2022 which can be obtained through the official website www.bsisyariah.co.id. The population of this study is the 2018-2022 financial reports at BSI Indonesiawhich have been published. The sample in this study is the annual financial statements of PT BSI Tbk for 2018-2022 which have been published on the official website of PT BSI Syariah Tbk using a purposive sampling technique. The results showed that partially showing Income, Fund Distribution, and Fee Based Income each variable had a significantly positive effect on return on assets at PT. BSI Indonesia. This has been proven by the value of tcount > ttable with a significance level of 0.05. Where tcount > ttable is 7.876 > 1.70814 and the significance value on Income